Optimized Modeling Strategies for the Parametrization of a Two-Parameter Friction Model Through Inverse Modeling of Conical Tube-Upsetting Tests - Michel Henze; Lena Koch; David Bailly; Marco Teller; Gerhard Hirt (Metals)
Friction is a critical influencing factor for a variety of forming processes, as it affects, for example, the required forming force. Complex models for the numerical description of friction often have two or more model parameters but lack appropriate calibration methods since calibration schemes developed for one-parameter models are not applicable. The objective of this work is to develop an evaluation method based on inverse modeling of the conical tube-upsetting test in order to allow for the parametrization of a two-parameter friction model, providing a unique solution for the model parameters. It is based on a comparison of the specimen’s outer contour for several points in time throughout the forming process according to the finite element model of the test. An optimization algorithm minimizes the deviation between the experimental and the simulated contour by adapting the friction model parameters. A two-parameter model is used that considers normal stress as well as relative velocity. First, purely numerical investigations show the necessity of a model adaption due to insufficient data. The modeling scheme is therefore adapted to consider data from two tests with different relative velocities. The results suggest a unique solution for the determination of the friction model parameters for purely numerical studies as well as for experimental conditions, comparing with the evolving contour of the conical tube-upsetting test specimen. Thus, this study presents a promising approach for the calibration of two-parameter friction models.